Phosphorus-modified biochar cross-linked Mg-Al layered double-hydroxide stabilizer reduced U and Pb uptake by Indian mustard (Brassica juncea L.) in uranium contaminated soil - Qiuling Yin; Peng Lyu; Guanghui Wang; Bing Wang; Yingjie Li; Zhongkui Zhou; Yadan Guo; Lianfang Li; Nansheng Deng (Ecotoxicology and Environmental Safety, 2022)
The decommissioning of uranium tailings (UMT) is usually accompanied by uranium (U) contamination in soil, which poses a serious threat to human health and ecological security. Therefore, the remediation of uranium pollution in soil is imminent from ecological and environmental points of view. In recent years, the use of biochar stabilizers to repair uranium tailings (UMT) soil has become a research hotspot. In this study, a novel phosphorus-modified bamboo biochar (PBC) cross-linked Mg–Al layered double-hydroxide composite (PBC@LDH) was prepared. The hyperaccumulator plant Indian mustard (Brassica juncea L.) was selected as the test plant for outdoor pot experiments, and the stabilizers were added to the UMT soil at the dosage ratio of 15 g kg−1, which verified the bioconcentrate and translocate of U and associated heavy metal Pb in the UMT soil by Indian mustard after stabilizer remediated. The results shown that, after 50 days of growth, compared with the untreated sample (CK), the Indian mustard in PBC@LDH treatment possessed a better growth and its biomass weight of whole plant was increased by 52.7%. Meanwhile, the bioconcentration factors (BF) of U and Pb for PBC@LDH treatment were significantly decreased by 73.4% and 34.2%, respectively; and the translocation factors (TF) were also commendable reduced by 15.1% and 2.4%, respectively. Furthermore, the Tessier available forms of U and Pb in rhizosphere soil showed a remarkably decrease compared with CK, which reached by 55.97% and 14.1% after PBC@LDH stabilization, respectively. Complexation, precipitation, and reduction of functional groups released by PBC@LDH with U and Pb described the immobilization mechanisms of biochar stabilizer preventing U and Pb enrichment in Indian mustard. As well as, the formation of U-containing vesicles was prevented by the precipitation of −OH functional groups with free U and Pb ions around the cell tissue fluids and vascular bundle structure of plant roots, thereby reducing the migration risk of toxic heavy metals to above-ground parts. In conclusion, this research demonstrates that the PBC@LDH stabilizer offers a potentially effective amendment for the remediation of U contaminated soil.